SUATU KAJIAN MOLEKULER KETERGANTUNGAN NIKOTIN - Agustina Setiawati (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2013)
Abstract: Nicotine, a simple chemical substance from tobacco, stimulates addiction byneuroadaptation inducing rewards system in human brain. Molecular mechanism of nicotineaddiction in rewards system are mediated by nicotinic acetylcholine receptor (nAChR) andactivate dopaminergic neuron. Thus, nicotine addiction are also induce other neurottransmitterand hormone release: norephinefrin, serotonin, opioid, glutamat and mono amine oxidase.Keywords: nicotine, addiction, rewards system.